Wine Making Technology Along With Types - Patnaik , Sudhansu (International Journal of Psychosocial Rehabilitation, 2019)
Wine is an alcoholic beverage made from fermented grape juice. The distinction between wine and beer, in terms of variations, is that beer is produced from distilled grapes, which are then aged. Wine is made from fruit and beer is made from grains, therefore, very simply. Wine making is the processing of wine, beginning with the collection of the grapes, the fermentation into alcohol and the finished beverage being bottled. Wine-making tradition extends through centuries. The wine and winemaking disciplines are classified as oenology. Also a wine-maker can be called a vintner. Grape growing is viticulture, and many types of grapes are found. The article presents a review of the potential of wine production from different fruits, wine classification and wine industry’s current status. This paper covered various classes of wine, such as grape wine, fruit wine, berry wine, vegetable wine, herb wine, raisin wine etc. Latest reports on the development of wine from various tropical and subtropical fruits such as strawberry, banana and apple cider.